AUDITORS' PERSONALITY IN INCREASING THE BURNOUT - Intiyas Utami; Ertambang Nahartyo (Universitas Hayam Wuruk Perbanas, 2013)
Auditors; personality is deemed to have some effects on the burnout. This factor is consideredimportant when the increase or decrease of burnout is identified. This research examinesthe moderating effect of type A personality on the relationship between role overloadand burnout in audit contexts. Most burnout researches have focused on the correlation ofvarious environmental factors, whereas individual differences factors also play an importantrole in the development of burnout. The data was done by means of survey on the participantsand this includes 58 auditors (junior, senior and manager) who work at public accountingfirms in Yogyakarta, Semarang, Jakarta and Palembang. The result shows that typeA personality intensifies the relationship between role overload and burnout.